Plato and Aristotle’s Educational Lessons from the Iliad - Cannatella, Howard James (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2006)
Of considerable importance in Plato and Aristotle’s educational outlook on the arts was Homer’s Iliad. This paper draws out some of the perceived weaknesses and strengths of this epic poem as it relates to the arguments in Plato’s Republic and Aristotle’s Poetics. I will attempt to do justice to Plato and Aristotle’s differing perspectives on the Iliad and their critique of art educational theory and practice. I will show why two philosophers with very different thinking on art education can still significantly affect art teaching practice today.